SEJARAH DOMINASI DOLAR AMERIKA SERIKAT DI DUNIA - Mochammad Afif Azhari Sutoyo; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted to see the process of how the United States dollar (USD) can dominate many countries and international organizations. Also to see the factors that strengthen the dominance of the USD so that it can be as it is now. The dominance of the United States dollar (USD) in the global monetary system has become the main concern and objective of the many countries. the dominance of the USD is earned through its use as the world's reserve currency, and the world's payment currency. the use of the usd as a world reserve currency has started since the 1920s, and the use of the usd as a global payment currency since the bretton woods agreement (1944). These two things make the US influence globally very strong, and make the USD a very important currency. The results of the study show that USD has dominance in the economies of every country and organization around the world. USD domination is not instantaneous, but through many journeys. The peak domination of USD came in gold standard era, when US emerged as the winner of World War II. At that time US has strongest economies, industry, and military power, that make US influence strong. Because of powerful US influence, US can dictate how the monetary system work and make USD as primary global Currency. One of the factors that has contributed to the domination of the USD is its use as the world's reserve currency and international payment currency. Keywords: Domination, Influence, United States Dollar.